The ANALYSIS FACTOR OF THE OCCUPATIONAL HEALTH SERVICE UTILIZATION AMONG FISHERMAN IN CITANGKIL DISTRICT, CILEGON CITY, BANTEN - Hayat, Fauzul (Bhamada Occupational Health and Safety Environment Journal, 2025)
Health challenges for informal sector workers such as fishermen are related to high cases of work-related diseases and work accidents in Indonesia. Government efforts are needed through the Occupational Health Unit (UKK) post services. This study aimed to determine the factors that cause the utilization of the occupational health services unit by fishermen in Warna Sari Village. A cross-sectional study design was selected, using purposive sampling in the research area. Data were collected from 60 fishermen using a structured questionnaire from February to March 2025. Chi-square test was used to univariate and bivariate analyzed data. Version 21 of SPSS was utilized in the analysis program. A total of 60 fishermen had participated in the study. The dominant age group was >30 years old (61.7%). The majority of respondents had a lower school education level (66.7%). Bivariate analysis showed a significant relationship between knowledge (p value = 0.034), health worker support (p value = 0.016), levels of awareness (p value = 0.000), need factor (p value = 0.005) with the occupational health services unit. A change in policy is required that places a larger emphasis on improving knowledge and increasing assistance from local public health services in order to encourage the fishing community to utilize the occupational health services in Warna Sari Village, Citangkil District, Cilegon City.